An AMBTC compression based data hiding scheme using pixel value adjusting strategy - Malik, Aruna; Sikka, Geeta; Verma, Harsh K. (Multidimensional systems and signal processing, 2018)
Image steganography is one of the most important research areas of information security where secret data is embedded in the images to conceal its existence while getting the minimum possible statistical detectability. To achieve a good tradeoff between the hiding capacity and image quality, more work needs to be further researched. In this paper, we propose high capacity data hiding scheme by employing the absolute moment block truncation coding (AMBTC) compression. It exploits the redundancy of blocks of the AMBTC-compressed image to embed the secret data. The pixel values of the AMBTC-compressed image are modified at most by one for hiding the secret data. Thus, it is able to maintain the stego-image quality after hiding the secret data. Experimental results validate the effectiveness of the proposed scheme and show that it outperforms various existing methods in terms of both hiding capacity and stego-image quality.